Handbook of Pultrusion Technology - Meyer, Raymond. author. aut Link
XII, 180 p.
Keywords: We have needed this book for some time. There is a very wide spectrum of management personnel, engineers in continuing education, specifiers, designers, graduate students--not to omit investors-who need this material as an intensive short course and reference work permanently at hand. Even in recession conditions the pultruded product business has grown by double-digit percentages, and this level of demand will continue as the U. S. infrastructure is renovated. Demand has stirred competition, in turn leading to product refinement. This technology development is taking place in materials, such as processable epoxy systems; in exotic but reliable production systems; and in mold/part complexity. The Handbook of Pultrusion Technology is essential to orient us in the fundamentals. The substance in Ray Meyer's treatment of this RP process is not available in any other compilation. Joseph S. McDermott, Manager Reinforced Plastics/Composites Institute The Society of the Plastics Industry, Inc. vii Preface Since my retirement five years ago I have had several oppor tunities to review my files and draft reports on pultrusion, especially for overseas clients. This book resulted from organ izing and updating these reports and filling in some of the gaps in my information.